Extended-range predictability of sudden stratospheric warming events suggested by mode decomposition - Wu, Zheng; Jiménez-Esteve, Bernat; Fondeville, Raphaël; Székely, Enikő; Obozinski, Guillaume; Ball, William T.; Domeisen, Daniela I. V. (2021)
Major sudden stratospheric warmings (SSWs) are extreme wintertime circulation events of the Arctic stratosphere that are accompanied by a breakdown of the polar vortex and are considered an important source of predictability of tropospheric weather on subseasonal to seasonal time scales over the Northern Hemisphere mid- and high- latitudes. However, SSWs themselves are difficult to forecast, with a predictability limit of around one to two weeks. The predictability limit for determining the type of event, i.e., wave-1 or wave-2 events, is even shorter. Here we analyze the dynamics of the vortex breakdown and look for early signs of the vortex deceleration process with lead times beyond the current predictability limit of SSWs. To this end, we employ a mode decomposition analysis to analyze potential vorticity (PV) equation on the 850 K isentropic surface by decomposing each term in the PV equation using the empirical orthogonal functions of the PV. The first principal component (PC) is an indicator of the strength of the polar vortex and starts to increase from around 25 days before the onset of SSWs, indicating a deceleration of the polar vortex. We then use a budget analysis based on the mode decomposition to characterize the contribution of the linear and the nonlinear PV advection terms to the rate of change (tendency) of the first PC. The linear PV advection is the main contributor to the PC tendency at 15 to 25 days before the onset of both types of SSW events. The nonlinear PV advection becomes important between 1 to 15 days before the onset of wave-2 events, while the linear PV advection continues to be the main contributor for wave-1 events. By linking the PV advection to the PV flux, we find that the linear PV flux is important for both types of SSWs from 15 to 25 days before the events but with different wave-2 spatial patterns, while the nonlinear PV flux displays a wave-3 wave pattern, which finally leads to a split of the polar vortex. The signals found here indicate that both the lead times for predicting the SSW onset and the lead times for predicting the type of the SSW event could potentially be extended beyond the current predictability limit of one to two weeks.